2021
DOI: 10.1111/eth.13194
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the concept of social behavior to interspecific interactions

Abstract: In pretty much any species, an individual's survival and reproduction depends crucially on the outcome of interactions with other individuals. Key interactions may take place between individuals of the same species but also between individuals belonging to different species. However, the most accepted definition of social behavior only considers interactions between conspecifics. Here, we argue that the distinction between intra-and interspecific interactions is largely artificial and hinders the integration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 190 publications
(247 reference statements)
1
16
0
Order By: Relevance
“…This suggests that the serotonin system has been co-opted to regulate aggression in general, both with individuals of the same or different species. The results thus contribute to the still relatively scarce evidence that interspecific interactions may be labelled as 'social' not only from a functional but also from a mechanistic perspective (Oliveira and Bshary, 2021).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This suggests that the serotonin system has been co-opted to regulate aggression in general, both with individuals of the same or different species. The results thus contribute to the still relatively scarce evidence that interspecific interactions may be labelled as 'social' not only from a functional but also from a mechanistic perspective (Oliveira and Bshary, 2021).…”
Section: Discussionmentioning
confidence: 58%
“…Social behaviours can have both positive effects, such as grooming and helping, and negative effects, such as competition and aggression (Tinbergen, 2012). The functional definition of social behaviour implies that recipients can be conspecifics as well as heterospecifics (Oliveira and Bshary, 2021). However, such an inclusive approach may be challenged on a mechanistic level unless it can be shown that intra- and interspecific interactions are governed by the same underlying mechanisms (Oliveira and Bshary, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring animal behaviour enables a better understanding of animal behavioural ecology in an evolutionary context e.g., inter- and intra-specific interactions such as competition and population dynamics [ 1 ]. Investigation of fine-scale animal behaviour can improve the understanding of animals’ functional response to the environment [ 2 ] and provide an important indicator of animal welfare [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The issue includes Perspective and Reviews papers asking how cooperative breeding may help or hinder coping with environmental change (Komdeur & Ma, 2021), highlighting the possibility that sociality is more widespread in marine habitats than usually assumed (Mazzei & Rubenstein, 2021), or how individual social competence may further the evolution of sociality and vice versa (Taborsky, 2021). Oliveira and Bshary (2021) propose to include interspecific relationships into social behaviour, and Bender (2021) outlines the potential for ethology to improve the evolutionary understanding of human medical problems. Original Research papers ask whether naked mole rats express caste differentiation (Siegmann et al, 2021), whether rats are aware of the ability of partners to reciprocate food donations (Schweinfurth, 2021), propose novel imaging techniques in the study of sociality (Jungwirth et al, 2021), show how collective actions can lead to diversification of behaviours (Green et al, 2021) and illustrate the importance of the early social environment for learning abilities in cichlids (Fischer et al, 2021) and later life attraction to conspecific odours (Schneeberger & Eccard, 2021).…”
mentioning
confidence: 99%